In-situ mineralization of carbon dioxide in a coal-fired power plant. Issue 4 (16th February 2016) - Helwani, Z.; Wiheeb, A. D.; Kim, J.; Othman, M. R.
ABSTRACT: Mitigation of anthropogenic carbon dioxide is needed in order to allow societies to maintain the existing carbon-based infrastructure, while minimizing the effects of carbon dioxide (CO2 ) on the earth eco-system. A system that consists of pressure swing adsorption and in-situ mineralization unit was introduced to capture carbon dioxide (CO2 ) from a 700 MW pulverized coal-fired power plant. Results from the work demonstrate that pressure swing adsorption for post-combustion carbon capture consumed the least energy, followed by biomass co-firing, pre-combustion cryogenic-membrane hybrid, and post-combustion monoethanolamine absorption. For carbon capture and sequestration, the pressure swing adsorption-fixation system was found to yield the lowest environmental burden factor, followed by off-site sequestration in deep sea and depleted underground oil/gas fields.